Una introducción a los debates jurídicos de la República de Weimar (Sección Abierta) - Carrillo Salgado, Augusto Fernando (2022)
The articles that have been published in Spanish on the Weimar Republic suffer from two weaknesses. On the one hand, they deal with very specific topics of this historical period; on the other hand, their writing is too dense or arid. These vicissitudes sometimes distance the reader from a topic that would undoubtedly enrich his education, especially in the areas of constitutional law and legal philosophy. In this sense, there is a need for a text that allows the reader to approach a stage in the history of Germany characterized by the important legal contributions. A document with the aforementioned characteristics would be a starting point for a deeper reading. The general aim of this paper is to provide an overview of the Weimar Republic. As a particular objective, the main ideas of Rudolf Smend, Hermann Heller, Carl Schmitt, and Hans Kelsen are explained. The methods used are historical, deductive, and analytical. The present work is composed of three main sections. First, an introduction to the Weimar Republic is presented. Second, the main ideas of the proposals of the four jurists mentioned are explained. Finally, the conclusions are presented and the epistemological validity of the legal debates in Weimar is highlighted.